A Lifetime of Trauma: Mental Health Challenges for Higher Education in a Conflict Environment in Afghanistan - Babury, Mohammed Osman; Hayward, Fred Manwarren (Education Policy Analysis Archives, 2013)
More than 30 years of war in Afghanistan have resulted in immense policy challenges to address the resulting mental health issues. The purpose of this policy analysis is to examine the potential role of higher education in addressing the pressing mental health problems in Afghanistan’s public universities and higher education institutions as a major policy challenge. We define and spell out the extent and nature of the mental health problems and policy issues involved, putting them in the context of students in a war environment. We discuss efforts by the leadership of the Ministry of Higher Education to respond to the physical damage of war and the resulting mental health crises in a setting of very scarce human and financial resources. We describe a system of higher education battered by years of war yet seeking to rebuild and raise quality even while the fighting continues. The conditions of the higher education system are described, as well as the scope, complexity and nature of mental health problems, and major challenges faced in trying to rebuild both the system and the lives of the higher education community. We spell out the immense challenges faced in rebuilding a system badly devastated by war while dealing with the tremendous human mental health toll experienced by its students, faculty, and staff. We conclude by setting out some possible directions, options and recommendations for responding to the mental health problems while recognizing the difficulties higher education faces in trying to respond to them.